2019
DOI: 10.1111/jne.12722
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 in the central amygdala is bioactive and co‐localised with glucagon‐like peptide‐1 receptor

Abstract: Neuronal circuits involving the central amygdala (CeA) are gaining prominence as important centres for regulation of metabolic functions. As a part of the subcortical food motivation circuitry, CeA is associated with food motivation and hunger. We have previously shown that interleukin (IL)‐6 can act as a downstream mediator of the metabolic effects of glucagon‐like peptide‐1 (GLP‐1) receptor (R) stimulation in the brain, although the sites of these effects are largely unknown. In the present study, we used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Tac2 is a neuropeptidergic gene enriched in medial and some lateral CeA neurons and modulates the expression of conditioned fear (Andero et al, 2014(Andero et al, , 2016. A recent study identified that ∼50% of Glp1r CeA neurons coexpress the cytokine interleukin-6 (IL-6) and that direct administration of IL-6 to the CeA could produce a subtle decrease in feeding, but the functional impact of IL-6 in combination with CeA GLP-1Rs is unclear (Anesten et al, 2019). The limited overlap we observed between Prkcd/Sst/Tac2 and Glp1r in the CeA suggests that the anorexigenic actions of peripherally-applied or intracerebral GLP-1R agonists are likely not due to the direct activation of these neurons, but do not preclude their activation through indirect network effects (Gabery et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tac2 is a neuropeptidergic gene enriched in medial and some lateral CeA neurons and modulates the expression of conditioned fear (Andero et al, 2014(Andero et al, , 2016. A recent study identified that ∼50% of Glp1r CeA neurons coexpress the cytokine interleukin-6 (IL-6) and that direct administration of IL-6 to the CeA could produce a subtle decrease in feeding, but the functional impact of IL-6 in combination with CeA GLP-1Rs is unclear (Anesten et al, 2019). The limited overlap we observed between Prkcd/Sst/Tac2 and Glp1r in the CeA suggests that the anorexigenic actions of peripherally-applied or intracerebral GLP-1R agonists are likely not due to the direct activation of these neurons, but do not preclude their activation through indirect network effects (Gabery et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Glp1r CeA neurons are located throughout the rostral-caudal axis with a non-significant increase in the middle third of the CeA and are more densely distributed in the CeM. Coincidently, the CeA also receives innervation from Preproglucagon (PPG, the precursor gene of GLP-1)-expressing neurons in the nucleus of the solitary tract and this innervation is most dense in the CeM (Llewellyn-Smith et al, 2011;Williams et al, 2018;Anesten et al, 2019). The functional and behavioral role of PPG inputs to the CeA are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that direct injection of GABA A receptor agonist in the CeA decreased food consumption (3) . According to Anesten et al (2019), the stimulation of glucagon-like peptide-1 receptors in the CeA nucleus reduces food intake (12) . Food consumption may be decreased by the microinjection of IL-6 into the CeA via the enhancement of glucagon-like peptide-1 receptors (12) .…”
Section: The Central Amygdala and Different Receptors As Well As Neur...mentioning
confidence: 99%
“…Nevertheless, the amygdala is seen as the main brain region with a critical role in feeding regulation (11) . The central amygdala (CeA) is a significant extra-hypothalamic region that has a determining impact on different physiological aspects and nutrition behaviours (12,13) . Several CeA inputs/outputs provide a vast connection surface for this core (14) .…”
mentioning
confidence: 99%
See 1 more Smart Citation